Perbedaan Persepsi Turki dan North Atlantic Treaty Organization Terhadap Ancaman Terorisme - Simbolon, Alvin Christopher (Indonesia Center for Middle East Studies, 2020)
This paper aims to describe the attitudes and policies taken by Turkey in dealing with the People's Protection Units (YPG); a Kurdish militia organization in Syria, which is seen as a terrorism threat to Turkey, but not to NATO. The lack of literature describing the dynamics of Turkey-NATO relations in terms of threat perception, especially those closely related to the YPG threat, is a gap that will be filled by the researcher in this paper. This paper argues that Turkey has taken actions and attitudes that tend to violate the boundaries of norms and values in the NATO alliance. Turkey played its part unilaterally in facing the YPG. This research uses the analytical framework of Intra-Alliance Opposition by Oya Dursun Ozkanca, which consists of three processes in the alliance. It describes when state tools are used in the alliance and for what purposes. It is hoped that this article will contribute to the development of the empirical and scientific literature on the Intra-Alliance Opposition using a case study of Turkey's foreign policy.